Advance care planning documentation adopted county-wide. Issue 2 (1st September 2011) - Chester, Helen; Johnson, Sally; Jones, Sally
Abstract : Introduction: The process of advance care planning is a vital and integral part of our practice. A need was identified for documentation to be developed locally to enable written records of patients' preferences and goals at the end of life which would also provide a tool for healthcare professionals. Aims: ▶ To develop an Advance Decision and Advance Statement form with guidelines for health and social care professionals. ▶ To develop patient information leaflets. ▶ To gain service user feedback about the use of the forms. ▶ To subject the forms to rigorous review by the hospice clinical governance committee, PCT and hospital trust committees before launching the forms and guidelines county-wide. Method: The draft forms were piloted for 3 months at the hospice. Feedback about ease of completion, appropriate timing of discussions and positive outcomes or problems relating to use of the forms, were collated. The forms and guidelines were then subject to review in all care settings, including trust resuscitation committees and solicitor. Results: All patients and staff involved in the pilot found the forms easy or very easy to complete. One patient died in his preferred place of care as a direct consequence. Most patients wished their GPs and hospital consultants to have a copy of their completed form. The forms are now progressing through the documentation committee; respective logos will then be added prior to their launch. Conclusion: Introducing the forms across all settings, accompanied by education and training, aims to raise the profile of advance care planning and improve exchange of information so that professionals in all settings are aware of a patient's documented wishes for end of life care.